Drift of the HIV-1 Envelope Glycoprotein gp120 toward Increased Neutralization Resistance over the Course of the Epidemic: a Comprehensive Study Using the Most Potent and Broadly Neutralizing Monoclonal Antibodies - Bouvin-Pley, M. (J Virol, 2014)
Extending our previous analyses to the most recently described monoclonal broadly neutralizing antibodies (bNAbs), we confirmed a drift of HIV-1 clade B variants over 2 decades toward higher resistance to bNAbs targeting almost all the identified gp120-neutralizing epitopes. In contrast, the sensitivity to bNAbs targeting the gp41 membrane-proximal external region remained stable, suggesting a selective pressure on gp120 preferentially. Despite this evolution, selected combinations of bNAbs remain capable of neutralizing efficiently most of the circulating variants.